Desenvolvimento de um Sistema Fotovoltaico com Rastreador Solar de um eixo instalado em uma propriedade rural conectado à Rede. - Berwanger, Diego (2019)
Currently, most of the energy produced in the world have non-renewable energy sources such as natural gas, coal, diesel or oil. However, these sources release green gases into the atmosphere as carbon dioxide (CO2), carbon monoxide (CO) and other gases in smaller quantities. An alternative is the use of renewable energy sources, such as photovoltaic solar energy. The great advantage in the use of solar energy is the production of electricity directly from sunlight with no emission of polluting gases, because it converts solar irradiation into electric energy, which can be used directly or stored for later use. Photovoltaic systems can be optimized through the use of solar tracker, since the more perpendicular the sun light achieves the panel surface, the greater its power and, consequently, the energy generation will increase. The main goal of this work was to design a photovoltaic solar system (SFV) with a tracker of one axis, design the SFV in CAD and evaluate the energy generation in SFV with solar tracker and fixed SFV. After develop the virtual prototype, the SFV system with solar tracker was assembled and installed in a rural property. Both SFV systems were connected to the local power distributor´s electrical grid as On-Grid systems. It was collected 21 days of energy generation data from the photovoltaic systems through energy meters with wireless transmission. The photovoltaic system without solar tracker obtained 21.84 kWh of generation, while the photovoltaic system with solar tracker reached 42 kWh of energy production. The use of solar tracking systems has a better cost-benefit because provides higher energy values compared to the system without the use of solar tracker.